The Relationship of Ethics and Politics From Al-Farabi's Perspective in The Philosophy of Islamic Education - Safitri, Fezi; Gunawan, Agus; Muhajir, Muhajir (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Abstract This research aims to describe the relationship between ethics and politics from Al Farabi's perspective in Islamic educational philosophy. The method used in this research is a descriptive qualitative approach. The data collection technique in this research is based on library research, namely the process of systematically identifying findings and analyzing documents containing information related to the research problem. Al-Farabi was one of the early philosophers who was concerned with the concept of ethics. AlFarabi is the successor of al-Kindi's intellectual tradition, but his competence, creativity, freedom of thought and level of sophistication are even higher. The book Ara Ahl Al-Madinah Al-Fadhilah leads to a discussion of politics, but the essence of both is actually to talk about ethics, namely state ethics so that a nation can become an ideal nation and in accordance with the Islamic vision. The final goal, namely societal happiness or social happiness, will be realized.